The Application of Virtual Reality in Cervical Spinal Surgery: A Review - Yan, Chunyi; Wu, Tingkui; Huang, Kangkang; He, Junbo; Liu, Hao; Hong, Ying; Wang, Beiyu (World neurosurgery, 2021)
In recent years, clinicians have used virtual reality (VR) to simulate real-world environments for medical purposes. The use of VR systems in the field of cervical spine surgery can lead to effective surgical training programs without causing harm to patients. Moreover, both imaging and VR can be used before surgery to assist preoperative surgical planning. VR devices have a variety of built-in motion sensors, therefore kinematic data can be recorded while users are wearing VR devices and performing some actions for the evaluation of cervical spine activity and exercise ability. Therapists have also applied VR to cervical spine rehabilitation and showed good results. At present, the application of VR systems in cervical spine surgery has great potential, but current research is insufficient. Here, we review the latest advancements in VR technology used in cervical spine surgery and discuss potential directions for future work.